2005
DOI: 10.1038/sj.npp.1300672
|View full text |Cite
|
Sign up to set email alerts
|

Group II and III Metabotropic Glutamate Receptors Suppress Excitatory Synaptic Transmission in the Dorsolateral Bed Nucleus of the Stria Terminalis

Abstract: Conditions such as anxiety, drug abuse, and post-traumatic stress disorder are thought to reflect alterations in central nervous system stress and reward circuitry. Recent evidence suggests a key component of this circuitry is the bed nucleus of the stria terminalis (BNST). In particular, regulation of glutamatergic transmission in the BNST plays a critical role in animal performance on anxiety tasks. Metabotropic glutamate receptors (mGluRs) have been implicated in stress and drug addiction and are known to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
72
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(75 citation statements)
references
References 58 publications
2
72
1
Order By: Relevance
“…To more directly test whether mGluR8 activation has effects on excitatory transmission in the BNST, we utilized the mGluR8 modulates excitatory transmission in the BNST HB Gosnell et al mGluR8-selective agonist DCPG, which has also been previously shown to depress excitatory transmission in this region (Grueter and Winder, 2005). Consistent with this, we found that a 20-min application of DCPG depressed excitatory transmission in the BNST as examined by field potential recordings (Figure 2a).…”
Section: Dcpg Depresses Excitatory Transmission In the Bnstsupporting
confidence: 66%
See 3 more Smart Citations
“…To more directly test whether mGluR8 activation has effects on excitatory transmission in the BNST, we utilized the mGluR8 modulates excitatory transmission in the BNST HB Gosnell et al mGluR8-selective agonist DCPG, which has also been previously shown to depress excitatory transmission in this region (Grueter and Winder, 2005). Consistent with this, we found that a 20-min application of DCPG depressed excitatory transmission in the BNST as examined by field potential recordings (Figure 2a).…”
Section: Dcpg Depresses Excitatory Transmission In the Bnstsupporting
confidence: 66%
“…In contrast to ionotropic glutamate receptors, the slower nature of mGluR signaling allows for potentially more long-lasting, adaptive changes in synaptic strength. Within the BNST, agonists to group I-III mGluRs depress glutamatergic transmission (Muly et al, 2007;Grueter and Winder, 2005;Grueter et al, 2006). Consistent percent depression by methoxamine is modestly but significantly attenuated in naive vs acutely restrained mice (stress: 18.0 ± 1.7 peak average percent depression vs 24.4 ± 3.0 for naive controls; po0.05, Student's t-test, n ¼ 4 to 5).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Within the amygdala, mGluR7 is localized to presynaptic terminals of glutamatergic neurons 179 and may act to inhibit glutamate release. 180 Callaerts-Vegh et al 181 compared mGluR7À/À mice with mGluR7 þ / þ littermate controls on a variety of tasks, including a conditioned emotional response (CER) procedure in which tone-shock pairings were introduced while the animals performed a previously trained nose-poke task in which nose pokes were reinforced by delivery of food pellets. Both groups of animals learned to nose poke equally well and both came to suppress nose poking during tone presentations equally quickly.…”
Section: Neurotransmitter Systemsmentioning
confidence: 99%